A string is stretched and fastened to two points at a distance 0
l
0 apart. Motion is started by
displacing the string in the form y = k sin πx
l
from which it is released at time t = 0. Show
that the displacement of any point on the string at a distance x from one end at time t is
given by k sin πx
l
cos πax
l
The equation of string is given by -
"\\dfrac{\\partial^{2}y}{\\partial t^{2}}=a^{2}\\dfrac{\\partial^{2}y}{\\partial x^{2}}" ".................................1)"
Sine the string is stretched between the two points (0,0) and "(l,0)" , hence the displacement of the string at these point will be zero .
"\\therefore y(0,t)=0............................................2)"
"and \\ y(l,t)=0...............................................3)"
since the string is released from rest hence its initial velocity will be zero .
"\\therefore \\dfrac{\\partial y}{\\partial t}=0\\ at\\ t=0 .....................................................4)"
since , the string is displaced from the initial position at time t=0 hence the initial displacement is given is
"y(x,0)=Ksin{\\dfrac{\\pi x}{l}}...........................................5)"
conditions (2), (3),(4),(5) are the boundary conditions
Let us now proceed to solve equation (1),
Let "y=XT...............................................6)"
where X is a function of "x\\ only" and T is a function of t only .
"\\dfrac{\\partial y}{\\partial t}=\\dfrac{\\partial (XT)}{\\partial t}=X\\dfrac{dT}{dt}"
"\\dfrac{\\partial^{2} y}{\\partial t^{2}}=\\dfrac{\\partial(X\\dfrac{dT}{dt})}{\\partial t}=X\\dfrac{d^{2}T}{dt^{2}}"
similarly, "\\dfrac{\\partial^{2} y}{\\partial t^{2}}=T\\dfrac{d^{2}X}{dx^{2}}"
substituting the above in equation (1) , we get
"X\\dfrac{d^{2}T}{dt^{2}}=a^{2}T\\dfrac{d^{2}X}{dx^{2}}" "\\implies" "XT^{''}=a^{2}TX^{''}"
Now making some cases , we get ,
"Case \\ 1)\\dfrac{1}{a^{2}}\\dfrac{T^{''}}{T}=\\dfrac{X^{''}}{X}=-P^{2}"
"i)" "\\dfrac{1}{a^{2}}\\dfrac{T^{''}}{T}=-p^{2}"
"\\dfrac{d^{2}T}{dt^{2}}+a^{2}p^{2}T=0"
Auxiliary equation is given by -
"m^{2}+c^{2}p^{2}=0"
"m=" "{\\pm}api"
"\\therefore CF=c_1cosapt+c_2sincpt"
"PI=0"
"\\therefore CF=c_1cos\\ apt+c_2 sin \\ {apt}"
"T=CF+PI"
"=c_1cos\\ apt+c_2 sin \\ {apt}.....................................7)"
"ii)" "\\dfrac{X''}{X}=-p^{2}" "\\implies" "\\dfrac{d^{2}X}{dx^{2}}+p^{2}X=0"
"\\dfrac{X''}{X}=-p^{2}"
Auxiliary equation is -
"m^{2}+p^{2}=0"
"m={\\pm}pi"
"\\therefore C.F=c_{3}cos(px)+c_4sin(px)" "=X..............................(8)"
hence , "y(x,t)=" "(c_1cos\\ apt+c_2 sin \\ {apt})(c_{3}cos(px)+c_4sin(px))................................9)"
"Case \\ 2)\\dfrac{1}{a^{2}}\\dfrac{T^{''}}{T}=\\dfrac{X^{''}}{X}=p^{2}"
"i)" "\\dfrac{1}{a^{2}}\\dfrac{T^{''}}{T}=p^{2}\\implies\\ \\dfrac{d^{2}T}{dt^{2}}-a^{2}p^{2}T=0"
Auxiliary equation is - "m^{2}-p^{2}a^{2}=0\\implies\\ m={\\pm}pa"
"\\therefore" "CF=c_5e^{apt}+c_6e^{-apt}"
"PI=0"
"\\therefore" "T=c_5e^{apt}+c_6e^{-apt}"
"ii)" "\\dfrac{X''}{X}=p^{2}"
"\\dfrac{d^{2}X}{dx^{2}}-p^{2}X=0"
Auxiliary equation is -
"m^{2}-p^{2}=0\\implies m={\\pm}p"
"\\therefore CF=c_{7}e^{px}+c_8e^{-px}"
"PI=0"
"\\therefore" "X=" "c_{7}e^{px}+c_8e^{-px}"
hence , "y(x,t)=(c_5cose^{pat}+c_6e^{-cpt})(c_7e^{px}+c_8e^{-px})...................10)"
"Case\\ III) \\dfrac{1}{a^{2}}\\dfrac{T^{''}}{T}=\\dfrac{X^{''}}{X}=0(say)"
"(i)" "\\dfrac{1}{a^{2}}\\dfrac{T^{''}}{T}=0\\implies T^{''}=0" or "\\dfrac{d^{2}T}{dt^{2}}=0"
Auxiliary equation is
"m^{2}=0\\implies m=0,0"
"\\therefore C.F=c_9+c_{10}t"
"PI=0"
"\\therefore" "T=c_9+c_{10}t"
"ii)" "\\dfrac{X^{''}}{X}=0(say)\\implies" "\\dfrac{d^{2}X}{dx^{2}}=0"
Auxiliary equation is -
"m^{2}=0\\implies m=0,0"
"\\therefore" "CF=c_{11}+c_{12}x"
"PI=0"
"\\therefore" "X=" "c_{11}+c_{12}x"
hence , "y(x,t)=(c_9+c_{10}x)(c_{11}+c_{12}x)........................................................11)"
Out of these three above solutions (9),(10)and (11), we have to choose the solution which is consistent with the physical nature of the problem . since we are dealing with problem on vibrations , the solution must contain periodic solution . hence the solutions which contains trignometric terms must be the solutions of given equations .
hence , solution (9) is the general solution of one -dimension wave equation given by the equation (1),
"now , y(x,t)=(c_1cos\\ {apt}+c_{2}sin\\ {apt})(c_3cos\\ px+c_4sin \\ px)"
Applying the boundary condition ,
"y(0,t)=0=" "(c_1cos\\ {apt}+c_{2}sin\\ {apt})c_{3}"
"\\implies" "c_{3}=0"
"\\therefore" "from \\ (9)," "y(x,t)=(c_1cos\\ {apt}+c_{2}sin\\ {apt})c_{4}sin\\ px"
again , now using the boundary conditions ,
"y(x,t)=0=(c_1cos\\ {apt}+c_{2}sin\\ {apt})c_{4}sin\\ pl"
"\\implies" "sinpl=0=sin{n{\\pi}}(n\\isin I)"
"\\therefore" "p=\\dfrac{n{\\pi}}{l}"
hence from (12), "y(x,t)=(c_1cos\\dfrac{n{\\pi}at}{l}+c_2sin\\dfrac{n{\\pi}at}{l})""c_{4}sin{\\dfrac{n{\\pi}x}{l}}"
"now \\" "(\\dfrac{\\partial y}{\\partial t})_{t=0}=\\dfrac{n{\\pi}a}{l}[-c_{1}sin\\dfrac{n{\\pi}at}{l}+c_{2}sin\\dfrac{n{\\pi}at}{l}]c_4sin\\dfrac{n{\\pi}x}{l}"
now again using boundary conditions ,
At t=0 ,
"(\\dfrac{\\partial y}{\\partial t})_{t=0}=0=\\dfrac{n{\\pi}c}{l}[c_2c_4sin\\dfrac{n{\\pi}x}{l}]"
"\\implies" "c_{2}=0"
"\\therefore" "from (13), \\ y(x,t)=c_1c_4cos\\dfrac{n{\\pi}at}{l}sin\\dfrac{n{\\pi}x}{l}"
"y(x,0)=ksin\\dfrac{{\\pi}x}{l}=c_1c_4sin\\dfrac{n{\\pi}x}{l}"
where "c_{1}c_{4}=k, n=1"
hence from (14), "y(x,t)=kcos\\dfrac{{\\pi}ax}{l}sin\\dfrac{{\\pi}x}{l}" which is required solution .
Comments
Leave a comment